Applying 'options thinking' to R&D valuation - Faulkner, Terrence W.
Terrence W. Faulkner outlines a practical way of applying the lessons from options pricing theory to some of the central problems of R&D management.
Used properly, options pricing can identify important sources of value that are missed by the traditional DCF approach.
There are situations in which options pricing theory provides a better basis for the valuation of R&D projects than the traditional discounted cash flow techniques used in most business cases. R&D managers need to be able to recognize those situations in which the two approaches are likely to give different answers, and they need to be aware of the different computational techniques that can be used for an options valuation of R&D projects. It is also important to understand the implications of an options approach for the formulation of both business and R&D strategy. "Options thinking" represents a practical way to apply the lessons from options pricing theory to some of the central problems of R&D management.
Keywords: R&D valuation